Oxidative stability and α-tocopherol retention in soybean oil with lemon seed extract (Citrus limon) under thermoxidation - Luzia, Débora Maria Moreno [UNESP]; Jorge, Neuza [UNESP] (My University, 2009)
The synergistic effect of lemon seed extract with tert-butylhydroquinone (TBHQ) in soybean oil subjected to thermoxidation by Rancimat was investigated, and the influence of these antioxidants on α-tocopherol degradation in thermoxidized soybean oil. Control, LSE (2,400 mg/kg Lemon Seed Extract), TBHQ (50 mg/kg), Mixture 1 (LSE + 50 mg/kg TBHQ) and Mixture 2 (LSE + 25 mg/kg TBHQ) were subjected to 180°C for 20 h. Samples were taken at time 0, 5, 10, 15 and 20 h intervals and analysed for oxidative stability and α-tocopherol content. LSE and Mixtures 1 and 2 showed the capacity of retarding lipid oxidation when added to soya oil and also contributed to α-tocopherol retention in oil heated at high temperatures. However, Mixtures 1 and 2 added to the oil presented a greater antioxidant power, consequently proving the antioxidants synergistic effect.
Keywords: Antioxidants; Citrus fruit; Thermoxidation; Tocopherol; alpha tocopherol; citrus fruit extract; soybean oil; tert butylhydroquinone; 2-tert-butylhydroquinone; antioxidant; hydroquinone derivative; plant extract; controlled study; degradation; heating; high temperature; lemon; lipid oxidation; nonhuman; oxidation; oxidative stability; plant seed; thermoxidation; chemistry; citrus fruit; heat; high performance liquid chromatography; oxidation reduction reaction; Citrus; Citrus limon; Glycine max; Chromatography, High Pressure Liquid; Hot Temperature; Hydroquinones; Oxidation-Reduction; Plant Extracts; Seeds; Soybean Oil; Vitamin E